All‐Solid‐State On‐Chip Supercapacitors Based on Free‐Standing 4H‐SiC Nanowire Arrays. Issue 17 (6th March 2019) - Li, Weijun; Liu, Qiao; Fang, Zhi; Wang, Lin; Chen, Shanliang; Gao, Fengmei; Ji, Yuan; Yang, Weiyou; Fang, Xiaosheng
Abstract: All‐solid‐state on‐chip SiC supercapacitors (SCs) based on free‐standing SiC nanowire arrays (NWAs) are reported. In comparison to the widely used technique based on the interdigitated fingers, the present strategy can be much more facile for constructing on‐chip SCs devices, which is directly sandwiched with a solid electrolyte layer between two pieces of SiC NWAs film without any substrate. The mass loading of active materials of on‐chip SiC SCs can be up to ≈5.6 mg cm −2, and the total device thickness is limited in ≈40 µm. The specific area energy and power densities of the SCs device reach 5.24 µWh cm −2 and 11.2 mW cm −2, and their specific volume energy and power densities run up to 1.31 mWh cm –3 and 2.8 W cm −3, respectively, which are two orders of magnitude higher than those of state‐of‐the‐art SiC‐based SCs, and also much higher than those of other solid‐state carbon‐based SCs ever reported. Furthermore, such on‐chip SCs exhibit superior rate capability and robust stability with over 94% capacitance retention after 10 000 cycles at a scan rate of 100 mV s −1, representing their high performance in all merits. Abstract : All‐solid‐state on‐chip SiC supercapacitors based on free‐standing SiC nanowire arrays are reported, which havespecific area energy and power density up to 5.24 μWh cm −2 and 11.2 mW cm −2, respectively, as well as robust stability with over 94% capacitance retention after 10 000 cycles at 100 mV s −1 .